Exploration of the influence mechanism of multi-generational interaction on young children’s socialization development – based on grandparents and parents co-parenting families - Daud, Mohd Najmi; Ziran, Li; Ashari, Asmidawati; Abdul Ghani, Mohamad Salleh (ACS Publisher, 2024)
Young children's socialization development begins at home, and the window of opportunity for this development is between the ages of three and six. In China, grandparents visit their children's homes to assist in caring for little children, a practice known as co-parenting, due to the influence of traditional family values and family economic strategy. The different parenting philosophies and lifestyles of the two generations of caregivers, grandparents and parents, add to the complexity and conflictual nature of multigenerational family interactions, which undoubtedly have an impact on and are closely related to the socialization and development of young children. This is especially true in cases where grandparents and parents are raising children together. In view of this, the purpose of this paper is to examine the mechanisms by which multigenerational interactions affect the socialization and development of young children. To this end, this paper approaches the issue from the perspective of family systems theory and provides a comprehensive review of the existing literature. It attempts to reveal how multigenerational interactions affect young children's socialization development and to explore the mechanisms by which multigenerational interactions work on young children's socialization development.